What happens after technology adoption?: gendered aspects of small-scale irrigation technologies in Ethiopia, Ghana, and Tanzania - Theis, Sophie; Lefore, Nicole; Meinzen-Dick, Ruth S.; Bryan, Elizabeth (Springer, 2018)
Diverse agricultural technologies are promoted to increase yields and incomes, save time, improve food and nutritional security, and even empower women. Yet a gender gap in technology adoption remains for many agricultural technologies, even for those that are promoted for women. This paper complements the literature on gender and technology adoption, which largely focuses on reasons for low rates of female technology adoption, by shifting attention to what happens within a household after it adopts a technology. Understanding the expected benefits and costs of adoption, from the perspective of women users in households with adult males, can help explain observed technology adoption rates and why technology adoption is often not sustained in the longer term. Drawing on qualitative data from Ethiopia, Ghana, and Tanzania, this paper develops a framework for examining the intrahousehold distribution of benefits from technology adoption, focusing on small-scale irrigation technologies. The framework contributes to the conceptual and empirical exploration of joint control over technology by men and women in the same household. Efforts to promote technology adoption for agricultural development and women’s empowerment would benefit from an understanding of intrahousehold control over technology to avoid interpreting technology adoption as an end in and of itself.